2021
DOI: 10.1097/scs.0000000000008001
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Inpatient Opioid Use Following Orthognathic Surgery

Abstract: Strategies to decrease postoperative opioid use are important for mitigating the immediate and long-term risks associated with their use. We aimed to investigate the impact of perioperative various factors on inpatient opioid needs for patients undergoing orthognathic surgery. Methods: This was a retrospective cohort study of all patients who underwent orthognathic surgery performed by the senior author from 2012 to 2018. Patients were grouped into intravenous (IV) acetaminophen and no-IV acetaminophen cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the present study, the total postoperative morphine consumption significantly decreased by 66.8% after administering the single dose of intravenous paracetamol when combined with the analgesic effect of NSAIDs and dexamethasone. Similarly, intravenous paracetamol was shown to effectively reduce opioid consumption after orthognathic surgery [ 20 ] and decreased the morphine requirement by 33% over 24 h after major orthopedic surgery [ 26 ]. As reported in a systematic review and meta-analysis, a single dose of 1 g intravenous paracetamol reduced pain up to 50% in 37% of patients and decreased the opioid requirement by 26% over 4 h compared with placebo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the total postoperative morphine consumption significantly decreased by 66.8% after administering the single dose of intravenous paracetamol when combined with the analgesic effect of NSAIDs and dexamethasone. Similarly, intravenous paracetamol was shown to effectively reduce opioid consumption after orthognathic surgery [ 20 ] and decreased the morphine requirement by 33% over 24 h after major orthopedic surgery [ 26 ]. As reported in a systematic review and meta-analysis, a single dose of 1 g intravenous paracetamol reduced pain up to 50% in 37% of patients and decreased the opioid requirement by 26% over 4 h compared with placebo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERAS encourages practitioners to decrease the use of opioid analgesics (to reduce the drug's side effects and the length of stay) and use opioid-sparing methods, such as regional anesthesia, paracetamol, NSAIDs, and other analgesic adjuvant drugs, instead [ 5 ]. There are some studies regarding using an MA strategy in orthognathic surgery [ 17 , 18 ] and the efficacy of intravenous paracetamol in orthognathic surgery and maxillofacial surgery pain control [ 19 , 20 ]. The results seemed to be effective for the pain relief and decreasing opioid usage.…”
Section: Introductionmentioning
confidence: 99%
“…To bolster our collective understanding of pain management, 28,29 an equal emphasis has been placed on providing continuing education about opioid stewardship through regular discussions and dissemination of information at multidisciplinary meetings, such as Hospital Quality and Improvement Committee (HQIC) and Pharmacy & Therapeutics (P&T) Committee. Moreover, IV acetaminophen administration has been identified as a putative opioid sparing option 30,31 in the surgical setting and hence, remains an integral part of multimodal analgesia. 32,33 At WCH, as observed between 2017 and 2021, while the number of surgical admissions for which IV acetaminophen was used to manage pain increased, the mean dose of IV acetaminophen used per surgical admission decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…3 Hence, the postoperative pain management of patients undergoing double-jaw surgery is usually based on local infiltration analgesia of mucosa (ie, intraoperative injection of local anesthetics) combined with a multimodal systemic analgesia regimen including opioids. [4][5][6] Previous study demonstrated the analgesic benefits of an ultrasound-guided V2 nerve block with 50% reduction in opioid consumption on postoperative day 2 in pediatric patients undergoing cleft palate surgeries. 7 More recently, encouraging results were published suggesting the analgesic effectiveness of this nerve block for orthognathic surgery in adults but with a low level of evidence.…”
Section: Introductionmentioning
confidence: 99%